CO2 UTILIZATION FOR MECHANOCHEMICAL CARBONATION OF CELESTINE - Turianicová, Erika (GeoScience Engineering, 2015)
Natural celestine (SrSO4) has been succesfully transformed into strontianite (SrCO3) via fast one-step mechanochemical carbonation utilizing gaseous CO2. The process was realized in the environment enriched with LiOH or NaOH additives. The mixtures were milled in a high-energy planetary ball mill for 40 min. The phases formed during the milling were characterized by different characterization techniques, such as X-ray diffraction (XRD) and infrared spectroscopy (FT-IR). The presence or absence of carbon or sulfur in the products was confirmed by CHNS analysis.